PENGARUH HARGA DAN PROMO GRATIS ONGKOS KIRIM TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA APLIKASI SHOPEE - Saputra, Bayu Yohan; Bustami, Taufik (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of Free Shipping Prices and Promos on Online Purchasing Decisions on the Shopee Application (Study on Management Students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu). This research is a quantitative study with a sample of 110 respondents, using accidental sampling technique. Data collection techniques using observation and questionnaires. Data analysis techniques using the classical assumption test, multiple linear regression, coefficient of determination (R2) and hypothesis testing. Price X_1 and Free Shipping Promo X_2 have an influence on Purchase Decision (Y), this can be seen in the F test which states the value of F_count>F_table, namely (248,282 > 3.930) and (sig α = 0.000 <0.000), so you can it can be concluded that H_3 is accepted, meaning that simultaneously the Price variable (X_1) and Free Shipping Promo (X_2) have a significant influence on online purchasing decisions (Y). From the results of the research conducted, the research conducted in this study showed that the X_1 price and the X_2 free shipping promo had an effect on online purchasing decisions (Y) for Management Students at the Faculty of Economics and Business, University of Muhammadiyah Bengkulu, users of the Shopee application. It is intended from the Correlation Coefficient and Determination that this study has an influence value of R = 0.526 and a determination of R2 = 0.277 where in this research there is a variable that is not examined at 0.277 or 27.7%. keywords: Price, Free Shipping Promo and Purchase Decision